Semiosis in Semiotics: How It is Formed and Developed - Awad , Samie; Yousef, Maisaa (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Semiotics is the process in which the three parts of a sign are united to form one integral mass. It studies the significance and their meaning as they are linked with other signs in a context. The main reason for these various expressions is theinfinite emerged meanings, which are stopless and constant and convey various implied meanings. Here lies the main concern of this research; how can we direct these significances to reach the real meaning of a text? So, the research tries to find out limits that restrict interpretations and their significances. yet, it allows the interpretator to interpret freely!